Bamlanivimab and Etesevimab administered in an outpatient setting for SARS-CoV-2 infection. (4th July 2022) - Bavaro, DF; Diella, L; Solimando, AG; Cicco, S; Buonamico, E; Stasi, C; Ciannarella, M; Marrone, M; Carpagnano, F; Resta, O; Carpagnano, GE; Palmieri, VO; et al.
ABSTRACT: The early administration of anti-SARS-CoV-2 monoclonal antibodies (mAb) could decrease the risk of severe disease and the need of inpatients care. Herein, our clinical experience with Bamlanivimab/Etesevimab for the treatment of early SARS-CoV-2 infection through an outpatient service was described. Patients with confirmed COVID-19 were selected by General Practitioners (GPs) if eligible to mAb administration, according to manufacturer and AIFA (Agenzia-Italiana-del-Farmaco) criteria. If suitability was confirmed by the Multidisciplinary Team, the patient was evaluated within the next 48–72 hours. Then, all patients underwent a medical evaluation, followed by mAb infusion or hospitalization if the medical condition had worsened. Overall, from March 29th to June 4th, 2021, 106 patients with confirmed COVID-19 were identified by GPs; 26 were considered not eligible and then excluded, while 9 refused treatment. Among the 71 remaining, 6 were not treated because of worsening of symptoms soon after selection. Finally, 65 received mAb therapy. All treated patients survived. However, 2/65 developed adverse events (allergic reaction and atrial fibrillation, respectively) and 6/65 needed hospitalization. By performing univariate logistic regression analysis, diabetes was the only risk factor for hospitalization after mAb administration [aOR = 9.34, 95%CI = 1.31–66.49, p = .026]. Importantly, subjects who worsened awaiting mAb were more frequently obese (OR = 16.66, 95%CI = 1.80–153.9, p = .013) and received home corticosteroid therapy for COVID-19 (OR = 14.11, 95%CI = 1.53–129.6, p = .019). Establishing a network among GPs and COVID units could be an effective strategy to provide mAb treatment to patients with early SARS-CoV-2 infection to reduce hospitalizations and pressure on healthcare systems.